Development and psychometric validation of the verbal affective memory test. Issue 9 (20th October 2016) - Jensen, Christian G.; Hjordt, Liv V.; Stenbæk, Dea S.; Andersen, Emil; Back, Silja K.; Lansner, Jon; Hageman, Ida; Dam, Henrik; Nielsen, Anna P.; Knudsen, Gitte M.; Frokjaer, Vibe G.; Hasselbalch, Steen G.
ABSTRACT: We here present the development and validation of the Verbal Affective Memory Test-24 (VAMT-24). First, we ensured face validity by selecting 24 words reliably perceived as positive, negative or neutral, respectively, according to healthy Danish adults' valence ratings of 210 common and non-taboo words. Second, we studied the test's psychometric properties in healthy adults. Finally, we investigated whether individuals diagnosed with Seasonal Affective Disorder (SAD) differed from healthy controls on seasonal changes in affective recall. Recall rates were internally consistent and reliable and converged satisfactorily with established non-affective verbal tests. Immediate recall (IMR) for positive words exceeded IMR for negative words in the healthy sample. Relatedly, individuals with SAD showed a significantly larger decrease in positive recall from summer to winter than healthy controls. Furthermore, larger seasonal decreases in positive recall significantly predicted larger increases in depressive symptoms. Retest reliability was satisfactory, r s ≥ .77. In conclusion, VAMT-24 is more thoroughly developed and validated than existing verbal affective memory tests and showed satisfactory psychometric properties. VAMT-24 seems especially sensitive to measuring positive verbal recall bias, perhaps due to the application of common, non-taboo words. Based on the psychometric and clinical results, we recommend VAMT-24 for international translations and studies of affective memory.